Perbandingan Tingkat Pengetahuan dan Sikap serta Praktik Pencegahan Skabies Pada Santri Pesantren di Banda Aceh dan Aceh Besar - Rahmatyawati, Cut; Asniar, Asniar; Atika, Syarifa (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Inadequate knowledge, attitude, and personal hygiene behavior contribute to the prevalence of scabies among students living together at the dorm of Islamic Boarding School (IBS). Moreover, the differences in the schools located in urban and rural areas may also increase these vulnerabilities. This study aimed to compare the level of knowledge and attitudes with the practices of scabies prevention among students of Islamic Boarding School in Banda Aceh and Aceh Besar.Methods: This research used a comparative study design with a cross-sectional approach, involving 86 students in Banda Aceh and Aceh Besar selected by stratified random sampling method. Data was collected using a questionnaire measuring knowledge, attitude, and perceived practice of scabies prevention, which was developed from Bloom's theory, and previously tested its psychometric properties. Data were analyzed using Independent Sample T-Test and Mann Whitney-U Test.Results: Based on the results of the study, it was found that the students of Aceh Besar had a greater experience of scabies (27.9%) than the students of Banda Aceh (18.6%). In the practice of personal hygiene, it is known that more than 85% of students have the habit of exchanging towels which is a factor in the occurrence of scabies. The results indicated a significant difference in students' attitudes in preventing scabies (p-value 0.025). However, there were no significant differences in the level of knowledge (p-value 0.067), personal hygiene habits (p-value 0.055), and the frequency of personal hygiene activities of students (p-value 0.490 α=0.05) in preventing scabies.Conclusion: There is a significant difference in attitudes towards scabies prevention among students in Banda Aceh and Aceh Besar. It is necessary to perform alternate interventions for students in both locations to increase positive attitudes in preventing scabies.